INFLUENCE OF CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM) AND PRICE EARNING RATIO (PER) ON STOCK RETURNS IN SERVICES SECTOR COMPANIES PROPERTY (Jurnal Ipteks Terapan, 2023)
This research analyzes the influence of the Current Ratio , Debt to Equity Ratio , Net Profit Margin , and Price Earning Ratio on Stock Returns both partially and simultaneously. This research uses a quantitative approach with a descriptive statistical analysis research model. The population was 49 companies, the sample selection used the Purposive Sampling technique so that the sample was 12 companies over a period of 6 years, so 72 data were obtained in the Property and Real Estate sector . The research results show that the classical assumptions have met the requirements. Partially (t test), (1) Current Ratio and Net Profit Margin have no effect and are not significant on Stock Returns , (2) Debt to Equity Ratio has a negative and significant effect on Stock Returns , (3) Price Earning Ratio has a positive and significant effect on Stock Returns . Simultaneously (F test) CR, DER, NPM and PER have a significant effect on stock returns . The coefficient of determination is 13.5% and the remaining is 86.5% Stock Return can be explained by other factors.